THE IMPACT OF SOCIAL MEDIA MARKETING ON CUSTOMER RELATIONSHIP DEVELOPMENT - Stojiljkovic, Aleksandra (Journal of process management and new technologies, 2019)
The research of digital marketing trends has shown that Social Media Marketing is at the very top of the list in popularity among digital marketing techniques on a global level. Numerous arguments which can be found in specialized and scientific literature illustrating the importance of Social Media Marketing in contemporary marketing practice, as well as the obvious topicality of this media, have been reason enough for further research. Considering the fact that customers and customer relationship development have become business imperative of every company, this marketing technique has been studied within the context of customer relationship development. The research results show that Social Media Marketing greatly influences customer relationship development.